Distribution of Salmonella spp. serotypes in poultry flocks in Abruzzo and Molise, Italy (2015-2020). (20th October 2021) - Perilli, M; Telera, GC; Sericola, M; Di Marcantonio, L; Marotta, F; Romantini, R; Del Matto, I; Pomilio, F; De Massis, F
Abstract: Issue/problem: The Italian National Health System has implemented a National Control Program for Salmonella in poultry populations in order to reduce the prevalence of infection. Starting from 2019, the control program has introduced health measures against Salmonella breeding flocks of Gallus gallus, positive to Salmonella Infantis, an emerging serotype at European level, and widespread along the entire poultry primary production chain. Description of the problem: Recent data from the European Union One Health 2019 Zoonoses Report published by EFSA, highlighted that most of the Salmonella isolates (70%) originated from broilers. Interestingly, Salmonella Infantis accounted for 29.7% of the total. Results: In the framework of the Italian Salmonella National Control Program the isolation of Salmonella spp. is carried out according to ISO 6579-1: 2017 from faeces, dust and boot socks. During the 2015-2020 period, testing in the Italian Regions Abruzzo and Molise was performed on 2, 791 samples and 5, 039 sample units. The percentage of samples positive to Salmonella spp. in Abruzzo and Molise was 16, 9% and 10, 1%, respectively. Out of 395 Salmonella spp. strains isolated, Salmonella Infantis was the most prevalent, representing the 54, 9% and 61, 9% for Abruzzo and Molise, respectively, followed by Salmonella Livingstone (18, 4%) for Abruzzo and (14, 4%) for Molise. Lessons: The record of Salmonella Infantis in the areas under study reflects the European trend highlighted by the EFSA 2019 Report and justifies the decision to increase the biosecurity measures in farms where this serotype is isolated and to proceed with destruction of positive animals according to the Regulation 1069/2009/EC. Key messages: Salmonella Infantis represents a risk for human health due to the presence of antimicrobial resistance genes that confer resistance to relevant antibiotics used in the treatment of human infections. Biosafety guidelines and disinfection practices on poultry farms should be improved in order to reduce the spread of this serotype, also considering its capability to form biofilm.